2014
DOI: 10.1371/journal.pone.0102695
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Divergence in the Catalytic Activity of the CAM-1, ROR1 and ROR2 Kinase Domains

Abstract: Receptor tyrosine kinase-like orphan receptors (ROR) 1 and 2 are atypical members of the receptor tyrosine kinase (RTK) family and have been associated with several human diseases. The vertebrate RORs contain an ATP binding domain that deviates from the consensus amino acid sequence, although the impact of this deviation on catalytic activity is not known and the kinase function of these receptors remains controversial. Recently, ROR2 was shown to signal through a Wnt responsive, β-catenin independent pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…The intracellular domains (ICDs) of RORs include a tyrosine kinase‐like domain followed by two serine/threonine‐rich domains flanking a proline‐rich domain, and a short C‐terminus end (Figure ). RORs are considered pseudokinases due to mutation in the canonical motifs found in bona fide kinases and the lack of detectable kinase activity in vitro using purified recombinant proteins . Mice mutated for both ROR1 and ROR2 phenocopy Wnt5a mouse mutants, indicating that ROR receptors bind to and transduce Wnt5a signaling …”
Section: Ror Signaling In Hematological Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intracellular domains (ICDs) of RORs include a tyrosine kinase‐like domain followed by two serine/threonine‐rich domains flanking a proline‐rich domain, and a short C‐terminus end (Figure ). RORs are considered pseudokinases due to mutation in the canonical motifs found in bona fide kinases and the lack of detectable kinase activity in vitro using purified recombinant proteins . Mice mutated for both ROR1 and ROR2 phenocopy Wnt5a mouse mutants, indicating that ROR receptors bind to and transduce Wnt5a signaling …”
Section: Ror Signaling In Hematological Cellsmentioning
confidence: 99%
“…RORs are considered pseudokinases due to mutation in the canonical motifs found in bona fide kinases and the lack of detectable kinase activity in vitro using purified recombinant proteins. 6,23 Mice mutated for both ROR1 and ROR2 phenocopy Wnt5a mouse mutants, indicating that ROR receptors bind to and transduce Wnt5a signaling. 20,21 ROR1 expression in healthy hematological tissue is restricted to the intermediate stage of B-lymphocyte precursors, called hematogones (CD10 + , CD19 + , dim CD45 + , CD34 − , and TdT − ).…”
Section: Ror S I G Naling In Hematolog I C Al Cell Smentioning
confidence: 99%
“…The cw82 (this study) and xd13 alleles (Song et al 2010) are missense mutations in the kinase domain, changing conserved glycines to charged amino acids. A recent study shows that CAM-1, unlike vertebrate Rors, possesses kinase activity in vitro (Bainbridge et al 2014), suggesting that the cw82 and xd13 alleles disrupt kinase activity. The finding that these kinase missense mutations have stronger effects on ALM polarity than the Class 2 mutations that are predicted to eliminate large parts of the intracellular domain is paradoxical.…”
Section: Resultsmentioning
confidence: 99%
“…However, a recent study using highly purified Ror2 shows that the protein lacks kinase activity in vitro (Bainbridge et al 2014). Ror2 is best characterized as a positive regulator of a non-canonical Wnt signaling pathway, functioning in mouse embryonic fibroblast (MEF) migration (Nishita et al 2006), in mouse hair cell orientation (Yamamoto et al 2008) and in Xenopus convergent extension (Hikasa et al 2002; Schambony and Wedlich 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Bainbridge et al have recently reported that ROR1 and ROR2 kinase domains have no catalytic activity. They believe that ROR1 kinase activity is due to its contamination with co-factors or other kinases [32]. Murphy et al studied a nucleotide binding property of different pseudokinases using a thermal-shift assay.…”
Section: Ror1 Structurementioning
confidence: 99%